RELATIONSHIP BETWEEN SMOKING BEHAVIOR AND MOTIVATION TO LEARN A TEENAGER - Kumboyono, Kumboyono (Jurnal Keperawatan, 2011)
The task of tenagger are growth and development that is looking for identity. In the search for identity, many influenced by the positive and negative. One of the negative influences on adolescent is a smoking behavior. Smoking activities undertaken during the learning process lasts may affect motivation to learn a teenager. Teenagers who still has a duty to learn, requires a strong motivation to achieve good learning performance. This study aims to prove the relationship of smoking behavior with adolescent learning motivation. This study was conducted using cross sectional conducted on 51 students of SMK Bina Bangsa Malang. Samples were selected using purposive sampling technique. The statistical testused was the chi-square, with a significance value of 0.238 (p value 0.05), and x2 is 0,287. The research Majalah Kesehatan FKUB results have meaning that there is no relationship between smoking behavior and motivation to learn ateenager. The conclusion from these studies, that most respondents have a mild smoking behavior with high learning motivation.